1999
DOI: 10.1523/jneurosci.19-15-06439.1999
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Release through Volume-Activated Channels during Spreading Depression

Abstract: Volume-sensitive organic anion channels (VSOACs) in astrocytes are activated by cell swelling and are permeable to organic anions, such as glutamate and taurine. We have examined the release of glutamate through VSOACs during the propagation of spreading depression (SD). SD was induced by bath application of ouabain in hippocampal brain slices and was monitored by imaging intrinsic optical signals, a technique that provides a measure of cellular swelling. The onset of SD was associated with increased light tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 47 publications
6
86
0
Order By: Relevance
“…This method might even be too slow to measure the regulatory volume decrease which is to a large extend mediated through astrocytic volume-sensitive organic anion channels. These anion channels activate within a few seconds following exposure to an osmotic stress (Basarsky et al 1999) The present data favour the glial cells as the major cell type involved in regulation of extracellular volume under physiological conditions. Thus the widening of the extracellular space in superficial cortical layers depends on cell coupling as shown by pharmacological manipulations and are suggested to be due to potassium syphoning through the glial network.…”
Section: Discussionsupporting
confidence: 69%
“…This method might even be too slow to measure the regulatory volume decrease which is to a large extend mediated through astrocytic volume-sensitive organic anion channels. These anion channels activate within a few seconds following exposure to an osmotic stress (Basarsky et al 1999) The present data favour the glial cells as the major cell type involved in regulation of extracellular volume under physiological conditions. Thus the widening of the extracellular space in superficial cortical layers depends on cell coupling as shown by pharmacological manipulations and are suggested to be due to potassium syphoning through the glial network.…”
Section: Discussionsupporting
confidence: 69%
“…Aside from system x c Ϫ, numerous mechanisms may be capable of releasing glutamate into the extrasynaptic compartment including vesicular release from astrocytes (Bezzi et al, 2004;Zhang et al, 2004), nonvesicular release from astrocytic gap junction hemichannels (Ye et al, 2003), volume-sensitive organic anion channels (Strange et al, 1996;Basarsky et al, 1999), or hydrolysis of N-acetylaspartylglutamate (Blakely et al, 1988;Zhou et al, 2005). Thus, models of brain functioning in the normal and diseased states need to account for the existence of high, steady-state levels of glutamate in the extrasynaptic space.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that glutamate released from astrocytes contributed to spreading depression in hippocampal slices. This glutamate was released in Ca 2+ free medium but blocked by 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), a Cl − channel inhibitor, indicating that glutamate could have been released through VRACs (Basarsky et al, 1999). Liu et al (2006) discerned swelling induced glutamate release from two different anion channels, the volume-sensitive outwardly rectifying (VSOR) chloride channels and the maxi-anion channels.…”
Section: Swelling/anion Channelsmentioning
confidence: 99%